2015
DOI: 10.15713/ins.jcri.69
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of osteoporosis in male and female patients between 30 and 75 years using orthopantomography

Abstract: Background: Osteoporosis is a systemic bone disease that is characterized by a generalized reduction of the bone mass. This bone disease exhibits microarchitectural degradation/disintegration of the bone scaffold that leads to increased bone fragility and more prone to fracture. Dental radiographs are one of the commonly used imaging modalities for teeth and jaw pathology. Aims and Objectives: The aim of this study was to assess the mandibular bone quality in panoramic radiographs for an initial evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Panoramic radiographs are the extra oral radiographs that provide overall hard tissue details of the maxilla and mandible which can be saved and stored for years. In general dental practice, dental panoramic radiography is used as a routine screening tool, assessment of radio morphometric indices may be helpful to identify low Bone Mineral Density (BMD) and can create awareness of osteoporosis [5] . Many studies have reported both positive and negative correlations between these indices of panoramic radiographs and osteoporotic conditions [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Panoramic radiographs are the extra oral radiographs that provide overall hard tissue details of the maxilla and mandible which can be saved and stored for years. In general dental practice, dental panoramic radiography is used as a routine screening tool, assessment of radio morphometric indices may be helpful to identify low Bone Mineral Density (BMD) and can create awareness of osteoporosis [5] . Many studies have reported both positive and negative correlations between these indices of panoramic radiographs and osteoporotic conditions [6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…Even though the gold standard to diagnose osteo porosis is a Dual-energy X-ray absorptiometry (DEXA) scan [4] , because of the cost and region-dependent availability these are considered less suitable for large-scale screening. Many studies on panoramic radiographs proposed radio morphometric indices as a diagnostic tool for osteoporotic conditions [5][6][7][8][9][10][11] . This study aims at assessing the reliability of radio morphometric indices of panoramic radiograph (Mental Index (MI), Antegonial Index (AI), Gonial Index (GI), Panoramic Mandibular Index (PMI), and Mandibular Cortical Index (MCI)) in diagnosing osteoporosis by measuring mandibular cortical width.…”
Section: Introductionmentioning
confidence: 99%